''Ethno…graphy?!? I can't even say it": Co‐designing training for ethnographic research for people with learning disabilities and carers. (21st September 2021) - Mikulak, Magdalena; Ryan, Sara; Bebbington, Pam; Bennett, Samantha; Carter, Jenny; Davidson, Lisa; Liddell, Kathy; Vaid, Angeli; Albury, Charlotte
Accessible Summary: We are a team of academic researchers, people with learning disabilities and carers. We worked together to design training materials for people with learning disabilities and carers to work as co‐researchers on research projects. The training was for doing a type of research called ethnography. When you do ethnography, you spend time with people to learn about their lives. In this article, we describe what we did and what we learnt. We think more people with learning disabilities and carers should be involved in research but many do not have the confidence to do it. Training can help with that. We also think that ethnography is a type of research that can be easier to do than other types of research. This is because ethnography uses the skills lots of us already have the following: watching, listening and talking to people. Abstract: Background: There is a strong ethical case and an urgent need for more participatory research practices in disability research but a lack of resources to support this. It is important to involve people with learning disabilities and carers at all stages, including when designing training for co‐research. Methods: We co‐developed training materials to support people with learning disabilities and carers to work as ethnographic co‐researchers and for academic researchers to facilitate co‐research. We focused on what people with learning disabilities and carers thought was important to learn. Findings: Whilst not all types of research methods are easy to democratise, ethnographic observation is a research method that lends itself well to participatory co‐research. Conclusions: For people to be able to meaningfully participate, research processes need to become more accessible and transparent. Training that considers the needs and priorities of people with learning disabilities and carers and addresses the confidence gap is key for meaningful co‐research.